Takotsubo Cardiomyopathy with Guillain-Barré Syndrome. Issue 3 (1st July 2017) - Gill, Dalvir; Ruiz, Vanessa Goyes; Dean, Ryan; Liu, Kan
Abstract : A 70-year-old woman presented with progressive lower extremity weakness and heaviness accompanied with chest pain. Troponin T was elevated, and an echocardiogram showed a left ventricular ejection fraction of 30% and a hypokinetic left ventricular apex. Neurophysiologic testing was consistent with Guillain-Barré syndrome, which was treated with intravenous immunoglobulin therapy. Repeat echocardiogram showed an improved left ventricular ejection fraction and no left ventricular wall motion abnormalities. Takotsubo cardiomyopathy is a rare complication of Guillain-Barré syndrome; less than 10 cases have been reported.